2012
DOI: 10.1007/s13277-012-0472-6
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of HOXA1 correlates with poor prognosis in patients with hepatocellular carcinoma

Abstract: HOXA1 overexpression is sufficient for malignant transformation of nontumorigenic epithelial cells. It is known that HOXA1, which was upregulated in squamous cell carcinomas, affects both cell growth and death. The forced expression of HOXA1 in human breast cancer cells results in increased cell growth activity. However, it has not been reported in hepatocellular carcinoma (HCC). In this study, we used immunohistochemistry to compare HOXA1 protein expression in HCC and normal liver tissues and further analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…7,[19][20][21][22] However, the role of lncRNA-HOTAIR in the chemoresistance of SCLC remains unknown. In this study, we initially identified lncRNA-HOTAIR as a regulator in chemoresistance of SCLC by qRT-PCR in H69/H69AR and H446/H446AR cells.…”
Section: Discussionmentioning
confidence: 99%
“…7,[19][20][21][22] However, the role of lncRNA-HOTAIR in the chemoresistance of SCLC remains unknown. In this study, we initially identified lncRNA-HOTAIR as a regulator in chemoresistance of SCLC by qRT-PCR in H69/H69AR and H446/H446AR cells.…”
Section: Discussionmentioning
confidence: 99%
“…Loss-of-function and lineage studies have implicated Hoxa1 in development of the inner ear, heart, neural crest specification, and hindbrain patterning (31)(32)(33). Growing evidence suggests roles for Hoxa1 in etiology of various cancers through modulation of cell proliferation, invasion, and metastasis (34)(35)(36)(37). These diverse functional roles for Hoxa1 appear to be at least partially related to its ability to influence key signaling pathways in differentiating cells (35).…”
mentioning
confidence: 99%
“…Previous studies have suggested that HOXA1 is overexpressed in various cancers, including breast, liver, oral and lung cancer (Chariot et al, 1996;Abe et al, 2006;Bitu et al, 2012;Zha et al, 2012). The forced expression of HOXA1 promoted oncogenic transformation by modulating the p44/42 MAP kinase pathway and bcl-2 in MCF-10 cells (Mohankumar et al, 2007).…”
Section: Discussionmentioning
confidence: 96%